2014
DOI: 10.1002/app.41118
|View full text |Cite
|
Sign up to set email alerts
|

Textile‐surface interfacial asymmetric polymerization

Abstract: This research demonstrated that polymerization of aniline on cellulose produces chiroptically active composites. Polymerization of aniline in the presence of cotton fibers consisting of chiral cellulose are performed to prepare a polyaniline (PANI)/cotton composite. The polymerization is conducted at the cotton interface. The resultant PANI/cotton composite shows chiroptical activity elucidated with diffuse reflectance circular dichroism. In this reaction, textile‐surface interfacial asymmetric polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Aniline sulfonic salt can be absorbed into the shell membrane by capillary effect [28]. The aniline molecules are arranged along the membrane prior to polymerization because of the intermolecular hydrogen bonding, or electrostatic interaction between aniline molecules and the protein of the shell membrane [13].…”
Section: Mechanismmentioning
confidence: 99%
“…Aniline sulfonic salt can be absorbed into the shell membrane by capillary effect [28]. The aniline molecules are arranged along the membrane prior to polymerization because of the intermolecular hydrogen bonding, or electrostatic interaction between aniline molecules and the protein of the shell membrane [13].…”
Section: Mechanismmentioning
confidence: 99%
“…21 Although the reaction selectivities were insufficient from the viewpoint of asymmetric synthesis, these two reports clearly indicated that nanocellulose has the potential to induce enantioselectivity, possibly owing to its inherent chiral nanoarchitecture. [22][23][24][25] As tremendous research effort has been focused on developing enantioselective catalysis, enantiodiscrimination based on naturally-occurring and renewable nanocellulose would be a promising development for a greener ne chemical industry. Herein, we report for the rst time that nanocellulose signicantly enhanced enantioselectivity and catalytic efficiency in proline-catalyzed aldol reactions, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%